(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The need for a legal framework that explains a decentralized system is compulsory to understand whether regulation could be useful and effective. Previous academic frameworks did not manage to explain the intimate development and success of a decentralized cryptocurrency system interpreting the difficult relationship among the various layers and activities. This essay tries to create a model based on swarm intelligence and stigmergy explaining the "organization without organizer". This innovative model can be useful to obtain a new framework that accounts for the different dynamics of cryptocurrencies and how regulation could affect different classes of actors. The distinction in Essential, Native and Metamorphic actors together with the concept of the "organization without organizer" could explain some dynamics and possibility of intervention.